The Psychotherapist, the Client, and Loneliness: A Mini Review - Ami Rokach (Ital Publication, 2018)
The present article examines the interaction between loneliness and psychotherapy; the salient features of psychotherapy, the needs of the lonely client, and the promise in the therapeutic process of being an agent of help to the lonely survive and aim at helping them emerge from their ordeal, emotionally strengthened and spiritually enriched.